Penerapan Strategi dan Metode Pembelajar IPS - Adisel, Adisel; Ramadhani, Fara Dila; Alexander, Loxsi; Paresga, Ilham (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this research is to know the strategies, approaches, methods, models and techniques of learning that have used the 2013 curriculum in implementing learning in schools. The method used here is the literature study method, this method is carried out by collecting data from existing books and journals as well as articles related to the problems discussed. Research results, models, approaches, strategies, methods, techniques, learning social studies (Social Sciences), are a very important element in learning. The quality of learning can be determined by how information is obtained and packaged, understood or applied by the teacher to students in the learning process. In conclusion, the Social Studies learning strategy is very necessary in a teaching and learning process so that it does not lag behind the current developments. So, models, approaches, strategies, methods, and learning techniques must be able to utilize information technology regarding social studies learning strategies in order to support the development of the learning process in education. Keywords: Methods, Models, Strategies, and Social Studies Learning